PERBANDINGAN MISKONSEPSI SISWA PADA TOPIK PEMBAHASAN RANGKAIAN LISTRIK BERDASARKAN JENIS SEKOLAH - Yasmine Khairunnisa (Universitas Lambung Mangkurat, 2018)
Abstract. This research aimed to acknowledge the existence of different misconceptions from students who are in other types of school on electric circuit matters. It is based on researcher’s effort in finding the cause of students’ misconception. This research was an experiment research with data collecting technique of online questionnaire. The sample was students at the age of 16-17 from public school, vocational school, and religious school, taken from population of all students from all those three types of school. Instrument used in this research was multiple choice questions about electric circuit developed by EPSE as many as 20 items. Data analysis technique was done by using Cross Tabulation in SPSS to see the difference of answers given by students based on school type. The result showed that religious school students get the highest misconception (100%) in an item about reading an ammeter in series circuit, public school students get 96.2% misconception in explaining the relationship between electric current and resistance in series circuit, and vocational school students get 86.4% misconception about electric voltage in parallel circuit. From the result, it can be seen that misconceptions owned by students from each type of school are different according to the method used in learning electric circuit in the school.